Psychology, Religion, and Spirituality - Nelson, James M. (Springer, 2009)
Over a century ago, psychologists who were fascinated with religion began to study and write about it. Theologians and religious practitioners have responded to this literature, producing a fascinating dialogue that deals with our fundamental understandings about the human person and our place in the world. This book provides an introduction to the important conversations that have developed out of these interchanges. The dialogue between psychology and religion is difficult to study for a number of reasons. First, it requires knowledge of both psychology and religion. People with a background in psychology often lack a solid understanding of the religious traditions they wish to study, and theologians may not be up to date on the latest developments in psychology. Second, it requires conceptual tools to organize the material and understand the basic problems involved in any attempt to connect the science of psychology with religion. These concepts can be found in many places, for instance in the writings of philosophers of science, but they are complex and often hard to follow for those without a proper theological and philosophical background. Finally, authors who write on the topic come to the study of psychology and religion from a variety of academic and personal backgrounds. This makes for wonderful diversity in conversations, but it makes understanding and mastery of the material quite difficult. Given these problems, why should we try to understand this dialogue? Along with many other scholars, I believe that psychology and religion both have things to say to each other that are mutually beneficial. Psychology offers religion the resources of science to improve the accuracy of its self-understanding and the methods it uses to pursue desired goals. Religion offers psychology a vast store of accumulated wisdom on the nature of the human person and how a good life might be achieved. As each field hears what the other has to say, there is a response or critique, and these are of vital importance as well. For instance, theological responses to psychological theory and research provide valuable corrections that can help the field avoid mistakes and misunderstandings. Accordingly, this book is written from a dialogical perspective, looking at some of the important conversations and critiques that have been exchanged between psychologists, theologians and religious practitioners. The word “and” in the title of this book reflects this dialogical aim.
Keywords: Psychology; Religion; Spirituality